2013
DOI: 10.1021/bi400126w
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Assembly of the Bacteroides fragilis Capsular Polysaccharide A Precursor Bactoprenyl Diphosphate-Linked Acetamido-4-amino-6-deoxygalactopyranose

Abstract: The sugar capsule Capsular Polysaccharide A (CPSA), which coats the surface of the mammalian symbiont Bacteroides fragilis, is a key mediator of mammalian immune system development. In addition, this sugar polymer has shown therapeutic potential in animal models of Multiple Sclerosis and other autoimmune disorders. The structure of the CPSA polymer includes a rare stereoconfiguration sugar acetamido-4-amino-6-deoxy-galactopyranose (AADGal) that we propose is the first sugar linked to a bactoprenyl diphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 41 publications
3
34
1
Order By: Relevance
“…1719,26 Reaction mixtures were prepared in a volume of 200 μ L, which contained 17.2 μ M UppS Bf , 10 mM 2CNA-GPP, and 75 mM IPP in OTG at 20 × CMC or DDM at 100 × CMC. The OTG reaction was quenched after 1.5 h with n -propanol, while the DDM reaction was allowed to continue for several hours.…”
Section: Resultsmentioning
confidence: 99%
“…1719,26 Reaction mixtures were prepared in a volume of 200 μ L, which contained 17.2 μ M UppS Bf , 10 mM 2CNA-GPP, and 75 mM IPP in OTG at 20 × CMC or DDM at 100 × CMC. The OTG reaction was quenched after 1.5 h with n -propanol, while the DDM reaction was allowed to continue for several hours.…”
Section: Resultsmentioning
confidence: 99%
“…The first sugar appended to BP 1 is N-acetyl-4-amino-6-deoxylgalactopyranose (AADGal) in a reaction catalyzed by the membrane-localized protein WcfS, to afford a bactoprenyl diphosphate-linked AADGal (BPP-AADGal 2 ). ( 14, 15 ) Each of the remaining sugars are expected to then be incorporated one at a time by the presumed glycosyltransferases WcfQ, WcfN and WcfP to provide Galf(1→3)-β-GalNAc(1→3)-β-4,6(Pyr)Gal-(1→3)-α-AADGal(1→PP-bactoprenyl 3 . ( 16 ) The Wzy polymerase then is expected to link the tetrasaccharide repeat unit from the AADGal to the GalNAc residue as many as 120 times to give the capsular polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the initiating hexose-1-phosphate transferase, WcfS, in CPSA repeat unit biosynthesis was biochemically elucidated utilizing isoprenoid analogues that enhanced the ability to track the production of bactoprenyl phosphate-linked reaction products (Figure 2). ( 14 ) These analogues were derived from a chemically synthesized 4-nitroaniline or 2-amideaniline geranyl diphosphate (2AA-GPP 4a, NAGPP 4b ) that was then elongated by the enzyme Undecaprenyl Pyrophosphate Synthase (UPPS) in the presence of isopentenyl diphosphate (IPP, 5 ). ( 15, 18 ) The long chain variable length isoprenoid product ( 6a-b ) of these reactions were then cleaved with a commercially available Alkaline Phosphatase to provide monophosphate substrate for WcfS (2AA-B(n)P, 7a , 4NA-B(n)P, 7b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campbell et al have shown that inhibition of TarO with tunicamycin sensitises methicillin-resistant S. aureus strains to beta-lactam antibiotics, implying a fundamental connection between teichoic acid biosynthesis and peptidoglycan assembly in S. aureus [17]. Other homologues in this phospho-sugar transferase family include a glucose-1-phosphate transferase WcaJ involved in colonic acid capsule biosynthesis in E. coli and C. crescentus [18], and transferase WcfS involved in B. fragilis capsular polysaccharide biosynthesis [19].…”
mentioning
confidence: 99%